2012
DOI: 10.1097/pas.0b013e318260cde7
|View full text |Cite
|
Sign up to set email alerts
|

Utility of GATA3 Immunohistochemistry in Differentiating Urothelial Carcinoma From Prostate Adenocarcinoma and Squamous Cell Carcinomas of the Uterine Cervix, Anus, and Lung

Abstract: Distinguishing invasive high-grade urothelial carcinoma (UC) from other carcinomas occurring in the genitourinary tract may be difficult. The differential diagnosis includes high-grade prostatic adenocarcinoma, spread from an anal squamous cell carcinoma (SCC), or spread from a uterine cervical SCC. In terms of metastatic UC, the most common problem is differentiating spread of UC to the lung versus a primary pulmonary SCC. Immunohistochemistry (IHC) for GATA binding protein 3 (GATA3), thrombomodulin (THROMBO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
102
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(117 citation statements)
references
References 18 publications
13
102
2
Order By: Relevance
“…Initial studies demonstrated that GATA3 immunostaining was seen in a limited number of tumor types: mammary carcinoma, urothelial carcinoma, and a minority of endometrial carcinomas [8,9,16]. Subsequent studies have expanded the list of GATA3-positive tumors to include occasional squamous cell carcinomas of the anus, cervix, and lung [11,12]. By performing immunohistochemistry on a large and diverse collection of salivary gland tumors, we found that approximately half were immunoreactive for GATA3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies demonstrated that GATA3 immunostaining was seen in a limited number of tumor types: mammary carcinoma, urothelial carcinoma, and a minority of endometrial carcinomas [8,9,16]. Subsequent studies have expanded the list of GATA3-positive tumors to include occasional squamous cell carcinomas of the anus, cervix, and lung [11,12]. By performing immunohistochemistry on a large and diverse collection of salivary gland tumors, we found that approximately half were immunoreactive for GATA3.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, GATA3 immunohistochemical staining is being used as a practical tool for diagnosing breast and urothelial carcinoma, particularly when these tumors present as distant metastases or are so poorly differentiated that they cannot be distinguished from other tumor types [10][11][12]. Various studies across a broad spectrum of diverse tumor types have confirmed the restricted expression of GATA3 staining to breast and urothelial origin, but these studies have curiously not included salivary gland neoplasms [1][2][3][4][5][6][7][8][9][10][11][12]. Mammary glands and salivary glands are both ectodermally-derived exocrine secretory structures that share many embryologic, histologic, and immunohistochemical features.…”
Section: Introductionmentioning
confidence: 99%
“…111 Many markers are useful for identifying HCC, including ARG1, glypican-3, HepPar-1, CD10, and polyclonal carcinoembryonic antigen (CEA). ARG1 is the most sensitive and specific marker for HCC, including poorly differentiated HCC, [77][78][79][80][81][82] whereas HepPar-1 is a sensitive, but not very specific, marker for HCC because its immunoreactivity has been reported in many other carcinomas. The diagnostic sensitivity of both ARG1 and HepPar-1 for identifying liver cell origin is more than 90%.…”
Section: Differential Diagnosis Of Ck7mentioning
confidence: 99%
“…These can exhibit strong CK5 and CK6 staining, absence of CK20, thrombomodulin and uroplakin III staining, and at times only focal CK7 positivity. 25,26 Staining patterns in metastatic bladder lesions can also vary from the primary lesion. A recent study compared expression of these markers in metastatic UC and suggested that uroplakin expression is lost but that CK7 staining and thrombomodulin staining are seen in 92% and 80% of metastatic UCs, respectively.…”
Section: 21mentioning
confidence: 99%